Salmonella sp. and Staphylococcus aureus contamination on food and hands of food handlers at Food Management Sites (TPM) Ulee Lheue Seaport - Nurliana Nurliana; Raudhah Raudhah; Teuku Reza Ferasyi; Sugito Sugito; Darmawi Darmawi; Wahyu Eka Sari (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
This study aims to determine the presence of Salmonella sp. and Staphylococcus aureus bacteria in rendang meat, fried chicken, fried fish, and omelets, as well as in the hands of food handlers in the Food Management Place (TPM). Ulee Lheue Sea Port by using laboratory tests. The study used five samples of food and five samples of food handlers' hands taken from the Food Management Place (TPM) of Ulee Lheue Seaport. Bacterial analysis on food samples in the laboratory using the Total Plate Count (TPC) method. Meanwhile, the Replicate Organism Direct Agar Contact (RODAC) method was used to examine food handlers' hands. Laboratory tests resulted from five food samples and five food handlers' hand samples that Salmonella sp. was found in omelets, and Staphylococcus aureus was found in beef rendang, fried chicken, fried fish, omelets, and hand samples of food handlers. It is necessary to conduct hygiene and environmental sanitation counseling at TPM around Port of Ulee Lheue.